Rekruitmen dan Seleksi Calon Sumber Daya Manusia Berbasis Merit Sistem - Yahya Romandoni, Ilham; Maunah, Binti; Syafi’i, Asrop (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Recruitment and selection of prospective Human Resources is a crucial stage in managing a quality workforce in every educational institution. The intense competition in the digital era is a reason for the need for educational institutions to continually update their services and the quality of their Human Resources in order to be able to compete. This research aims to define, plan, implement and assess the recruitment and selection of human resource candidates using achievement-based methods by examining prospects, difficulties and the results of previous research. This research uses a literature review approach. The data sources for this research come from Google Scholar, ChatGPT, You.com, Copilot and the Education Management journal database. The data analysis technique uses thematic analysis to examine the relationships and implications of the findings. The results of the analysis are then synthesized and interpreted to draw conclusions. The results of this research state that the merit system-based recruitment and selection of Human Resource candidates is an essential approach in building the excellence of educational institutions through the presence of a quality workforce. Through this system, Human Resources are selected based on their qualifications, abilities and achievements, not because of subjective factors or personal interests. In addition, a merit-based approach provides a fair opportunity for all individuals to compete equally in obtaining positions in educational institutions. This system also has a long-term positive impact on the productivity and performance of educational institutions as a whole